On the existence of additional miscibility gap in NicCu₁₋c fcc alloy - Timoshevskii, A.N.; Yanchitsky, B.Z.; Korenivski, V. (Functional Materials, 2012)
Magnetic and interatomic interaction parameters for NicCu₁₋c alloys were calculated by ab-initio full potential linearized augmented plane wave method. Using these parameters solid state part of the phase diagram was constructed in mean-field approximation for Hamiltonian containing both chemical and magnetic interactions. Calculations revealed the presence of additional stable miscibility gap due to magnetic interactions between Ni atoms. Within this approach a general condition for existence of such a gap was derived.